Feline large granular lymphocyte lymphoma: An Italian Society of Veterinary Oncology (SIONCOV) retrospective study. (29th May 2017) - Finotello, R.; Vasconi, M. E.; Sabattini, S.; Agnoli, C.; Giacoboni, C.; Annoni, M.; Dentini, A.; Bettini, G.; Guazzi, P.; Stefanello, D.; Bottero, E.; Mesto, P.; et al.
Abstract : Feline large granular lymphocyte (LGL) lymphoma is an uncommon subtype of lymphoma characterized by a grave prognosis and scarce response to chemotherapy. There are limited reports on clinico‐pathological and prognostic factors. One‐hundred and 9 cats with newly diagnosed LGL lymphoma that underwent initial staging (including hematology, serum biochemistry, thoracic radiographs and abdominal ultrasound), and followed‐up were retrospectively evaluated. LGL lymphoma was localized within the gastrointestinal tract with or without extra‐intestinal involvement in 91.7% of the cases, and at extra‐gastrointestinal sites in 8.3%. Symptoms were frequent. Anemia (31.2%) and neutrophilia (26.6%) were commonly observed, and 14 (12.8%) cats had neoplastic circulating cells. Frequent biochemistry abnormalities included elevated ALT (39.4%) and hypoalbuminemia (28.4%). Twenty (54.1%) of 37 cats had elevated serum LDH. Treatment varied among cats, and included surgery (11%), chemotherapy (23%), corticosteroids (38.5%) and no treatment (27.5%). Median time to progression (MTTP) was 5 days, and median survival time (MST) 21 days. MST was significantly shorter in the case of substage b, circulating neoplastic cells, lack of chemotherapy administration, and lack of treatment response. A small subset of cats (7.3%) survived more than 6 months, suggesting that a more favorable clinical course can be found among LGL lymphoma patients.